Infection prevention and control considerations regarding ventilation in acute hospitals - Hilary Humphreys (Elsevier, 2021)
Summary: Infection prevention and control team members (IPCTM) are often intimidated by aspects of ventilation as they relate to healthcare, because they consider them technical and outside their area of comfort and expertise. However, engineers, estates departments and planners need IPCTM input to ensure appropriate design and use. The main areas of importance centre on the operating theatre, the provision of air-controlled ventilated isolation rooms, and how to respond to major outbreaks/pandemics. Concentrating on basic principles of infection prevention and control, developing relationships with key departments and individuals, and applying best practice to these and other areas as they arise, are of great value. Some background, information and suggestions are provided for IPCTM with a view to providing simple practical advice in these areas.